Prevalencia y factores asociados al ingreso a UCI en niños hospitalizados por neumonía adquirida en la comunidad en Iquitos, 2024 - Flores Caballero, Percy Fernando (2025)
Introduction: Community-acquired pneumonia (CAP) is one of the first pathologies with the highest frequency and risk of death in children, especially in children under five years of age. Globally, it represents a high health burden, especially in regions with socioeconomic and geographic limitations, such as Loreto, Iquitos. CAP can evolve into severe cases that require transfer to pediatric intensive care units (PICU), increasing the costs of care and the risk of severe complications. However, there is a knowledge gap on the frequency and factors associated with these admissions in this specific region. Objective: To determine the prevalence and factors associated with PICU admission in children hospitalized for community-acquired pneumonia in Iquitos, 2024. Study Population: The sample will be a census sample and will include 102 patients between 1 and 12 years old hospitalized for CAP in the Regional Hospital of Loreto, between January and December 2024. Method: The study will be observational, analytical, retrospective and cross-sectional. Results: The data collected will be organized in Excel spreadsheets and imported into SPSS IBM Statistics v27 statistical software for analysis. Univariate, bivariate and multivariate analyses will be performed. Results will be presented in tables and graphs to facilitate interpretation. Conclusions: This study aims to generate scientific evidence on the prevalence and factors associated with ICU admission in children with CAP in Iquitos, contributing to the development of clinical management strategies adapted to the regional context and optimizing pediatric care.